2021
DOI: 10.3389/fonc.2021.620644
|View full text |Cite
|
Sign up to set email alerts
|

More Favorable Short and Long-Term Outcomes for Screen-Detected Colorectal Cancer Patients

Abstract: BackgroundScreening significantly reduces mortality from colorectal cancer (CRC). Screen detected (SD) tumors associate with better prognosis, even at later stage, compared to non-screen detected (NSD) tumors. We aimed to evaluate the association between diagnostic modality (SD vs. NSD) and short- and long-term outcomes of patients undergoing surgery for CRC.Materials and MethodsThis retrospective cohort study involved patients aged 50–69 years, residing in Veneto, Italy, who underwent curative-intent surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
4
18
0
Order By: Relevance
“…Survival probabilities for patients with screen-detected CRC have been previously reported in the context of pilot studies prior to implementation of population-based screening programmes 8 , 9 and in a few regional and nationwide studies conducted during the first years of screening roll out, mostly in the early 2000s. 7 , 10 , 11 , 12 , 13 , 14 , 15 These studies reported five-year overall survival (patients aged 50-69, 50-74, or 50-79) of around 80% or above, ie, close to or within the range of our findings.…”
Section: Discussionsupporting
confidence: 87%
“…Survival probabilities for patients with screen-detected CRC have been previously reported in the context of pilot studies prior to implementation of population-based screening programmes 8 , 9 and in a few regional and nationwide studies conducted during the first years of screening roll out, mostly in the early 2000s. 7 , 10 , 11 , 12 , 13 , 14 , 15 These studies reported five-year overall survival (patients aged 50-69, 50-74, or 50-79) of around 80% or above, ie, close to or within the range of our findings.…”
Section: Discussionsupporting
confidence: 87%
“…The cancer diagnostic route taken by patients with MS was previously unknown; however, less breast and colorectal cancer screening detection has been observed in other populations with high comorbid disease burden, 7,33 and less cancer screening has been documented in the broader MS population. [8][9][10]34 Patients with MS and severe disability are less likely to have annual mammograms and screening colonoscopies over age 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…We studied 3 interrelated outcomes from the cancer diagnostic process: diagnostic route, cancer stage, and diagnostic interval. Whether a patient is diagnosed through a screening or a symptomatic route is associated with the cancer stage at diagnosis 7,21,22 and presenting symptoms are partly a function of cancer stage. Symptom severity can influence the urgency with which the problem is investigated, thereby influencing the length of the diagnostic interval 23 and, concurrently, longer diagnostic intervals have been associated with advanced stage cancer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the sensitivity analysis including only known stage are more conservative than our main analysis (although less so for Duke D in particular). The fact that screen-detected cancers are more likely to have stage recorded ( 21 ) confers a conservative bias, increasing the relative risk associated with screening. The results of the sensitivity analysis using inverse probability weighting were similar but not identical to those of our main analysis.…”
Section: Discussionmentioning
confidence: 99%